2022
DOI: 10.1177/23779608211054814
|View full text |Cite
|
Sign up to set email alerts
|

Managing Type 2 Diabetes: Beliefs and Daily Practices in First Generation Asian Indians in the United States

Abstract: Introduction Diabetes management and control remain poor in Asian Indians (AI) and is influenced by personal beliefs and cultural practices. Since AIs have a high prevalence of diabetes and are more likely develop complications earlier than any other ethnic group, understanding their beliefs and practices of diabetes management is essential. The purpose of this study was to examine and understand beliefs and practices about diabetes self-management in first-generation AI Hindus and Sikhs. Method Interpretative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
2
0
0
Order By: Relevance
“…It was also interestingly found that FGD participants proposed to include family members in education. This finding was consistent with the previous study [ 46 ]. Participants reported that receiving guidance and support from physicians helped them to perform optimal DMSCPs.…”
Section: Discussionsupporting
confidence: 94%
“…It was also interestingly found that FGD participants proposed to include family members in education. This finding was consistent with the previous study [ 46 ]. Participants reported that receiving guidance and support from physicians helped them to perform optimal DMSCPs.…”
Section: Discussionsupporting
confidence: 94%
“…Park et al (2022) found that patients with T2DM trusted health information when explained by family members more than providers, which may be why promotoras previously described have improved diabetes self-management. Similar thoughts on barriers and motivators regarding family and diabetes selfmanagement have been described in qualitative literature focusing on black and South Asian communities (Deol et al, 2022;Lee et al, 2019;Rao et al, 2021). This suggests the desires expressed in our study are generalizable to other ethnic minorities facing health disparities.…”
Section: Diabetes Affects the Whole Familysupporting
confidence: 80%